La Mostra internazionale francescana ad Assisi del 1927 - Alessandro Paolo Lena (Artes)
During the 1920s and 1930s, several exhibitions were held in Italy showcasing Modern-era sacred art, sparking lively discussions between artists and clergy about the characteristics of religious artworks and their display. In order to assess the role these exhibitions played in the political and cultural context of the time, this paper examines the case of the International Franciscan exhibition held in Assisi in 1927. Organised for the seventh centenary of Saint Francis’ death, the show sought to present the features of contemporary Franciscan art along with a selection of works from the Treasury as a prelude to the opening of the Treasure Museum within the Sacred Convent. At the same time, as part of the centenary celebrations, the exhibition bore significant political significance in the framework of Fascist ideology’s efforts to promote the veneration of Francis of Assisi in order to convey and celebrate the myth of Italian nationality through the figure of the saint.